Gambaran Kadar Hemoglobin pada Remaja Putri; Studi Kasus di SMP Negeri 27 Padang - Burhan, Ida Rahmah; Firdawati, Firdawati; Asy Syukri, Muhammad Hasbi; Fauziah Nur; Fikri Rahman; Putri, Rizqy Nurfathonah; Asyifa Delfilaura; Rahadi, Didan Ariadapa; Dharma, Fitri Yeni (Andalas Obstetrics And Gynecology Journal, 2025)
Introduction: The prevalence of anemia in adolescent girls worldwide is reported to be around 40-88%. Adolescent girls with anemia can affect work productivity or academic ability at school due to a lack of enthusiasm for learning and focus. Anemia in adolescent girls can continue throughout their lives and put them at risk of becoming anemic pregnant women who can give birth to premature babies and leading to stunting. This study aims to determine the description of hemoglobin levels in female adolescents at SMP Negeri 27 Padang. Method: The research was descriptive, using a sample of 116 adolescent girls selected by proportionate stratified random sampling. Hemoglobin levels were examined using the Point of Care Testing (POCT) method using capillary blood. Results: The results show that most hemoglobin levels are normal, namely 60 respondents (51,7%), low hemoglobin levels are 55 respondents (47,4%), and high hemoglobin levels are 1 respondents (0,9%). Conclusion: It can be concluded that hemoglobin levels among adolescent girls at SMP Negeri 27 Padang generally have normal hemoglobin levels. Keywords: Adolescent girls, anemia, hemoglobin